VD_FINDINFO HC / 2015 / 824 vom 12. August 2015 - VD Tribunal cantonal (2015)
RÉCUSATION, EXPERT, DOMMAGE IRRÉPARABLE | 183 al. 2 CPC (CH), 183 CPC (CH), 319 CPC (CH), 319 let. b ch. 2 CPC (CH), 319 let. b CPC (CH)